PENGARUH PDRB DAN ASET TERHADAP PENERIMAAN DAERAH SERTA IMPLIKASINYA PADA KINERJA KEUANGAN PEMERINTAH KABUPATEN/ KOTA DI JAWA TENGAH - Indriyani, Indriyani; Pandansari, Tiara (Media Ekonomi, 2016)
This research was conducted to obtain evidence related to the Influence of Gross Regional Domestic Product and Assets in Revenue And Their Implications On Financial Performance in Regency/ City in Central of Java. Financial performance is calculated using the fiscal capacity, fiscal decentralization ratio independence ratio , the ratio of the effectiveness and efficiency ratios . The research was conducted and located in 35 Regency / City in Central of Java, consists of 29 regency and 6 city . The data used in the form of APBD and realization APBD, Balance Sheet and GDRP in Central of Java in 2008 to 2011 . Tests performed by using regression analysis . The results of this research indicate that GDRP have positive and significant impact on local revenues, Assets do not affect to the local revenue and Local revenue is negative and significant effect on financial performance. Testing for local revenue as variable that mediate GDRP and assets against financial performance was tested using regression analysis of variables mediating the causal step method and obtained results that did not mediate the relationship GDRP and assets with financial performance. Keywords : GDRP, assets, local revenues, financial performance